Doing without concepts - Machery, Edouard (Oxford University Press, 2009)
Concepts in psychology -- "Concept" in psychology -- Evidence for the existence of concepts -- What is a psychological theory of concepts? -- Alternative characterizations of the notion of concept -- Concepts in philosophy -- "Concept" in philosophy -- Concepts in philosophy versus concepts in psychology -- How are the psychological and the philosophical theories of concepts connected? -- Peacocke's simple account -- How are the psychological and the philosophical theories of concepts connected? the foundationalist account -- The heterogeneity hypothesis -- The received view -- The heterogeneity hypothesis -- Hybrid theories of concepts -- Three fundamental kinds of concepts: prototypes, exemplars, theories -- The classical theory of concepts -- The prototype paradigm of concepts -- The exemplar paradigm of concepts -- The theory paradigm of concepts -- Alternative views of concepts -- Three theoretical entities that have little in common -- Multi-process theories -- Multi-process theories -- Examples of multi-process theories -- Categorization and concept learning -- Categorization and concept learning -- Studying categorization and concept learning -- Evidence for the existence of prototypes -- Evidence for the existence of exemplars -- Evidence for the existence of theories -- Organization of the categorization processes and of the concept learning processes -- Induction, concept combination, neuropsychology -- Induction -- Concept combination -- Neuropsychology -- Concept eliminativism -- Two inconclusive arguments against the notion of concept -- Natural kinds and scientific eliminativism -- The argument for the elimination of "concept" -- Objections and replies